Effectiveness and safety of nonablative fractional laser and infrared bipolar radiofrequency for treating periorbital wrinkles. (17th November 2022) - Wu, Xianglei; Cen, Qingqing; Zhu, Jiafang; Shang, Ying; Lin, Xiaoxi
ABSTRACT: Non-ablative fractional laser (NAFL) and radiofrequency (RF) are popular for treating periorbital wrinkles owing to short downtime and low risk of side effects. To compare the effectiveness and safety of infrared bipolar radiofrequency (IR-RF) and NAFL, including 1540 nm Er: glass and 1927 nm thulium-doped laser, to determine the better option for clinical treatment of periorbital wrinkles. Twenty-seven patients assigned to 3 groups underwent split-face treatment. Two of the three treatments were randomly selected for patients in each group: IR-RF, 1540 nm Er: glass NAFL, and 1927 nm thulium-doped NAFL. Therapeutic outcomes were subjectively and objectively evaluated six months after the last treatment. Side effects and pain evaluations were conducted. Fitzpatrick wrinkle scores revealed no statistical difference for IR-RF, whereas the NAFL-treated sides exhibited significant improvements (p < .05). VISIA analysis of skin texture showed similar results. In IR-RF-treated sides, patients over 50 years old exhibited significant improvements compared with those below 50 (p < .05). The sample size was small. More objective evaluations like photometer measurements are required. NAFL is effective and safe for improving periorbital wrinkles, but IR-RF might be more suitable for elderly patients, particularly those with low pain tolerance.